Interval Oscillation of Damped Second-Order Mixed Nonlinear Differential Equation with Variable Delay under Impulse Effects - Muthulakshmi, V.; Manjuram, R. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study the oscillatory behavior of damped second-order mixed nonlinear differential equation with variable delay under impulse effects. By using Riccati transformation technique, integral averaging method and some inequalities, we obtain sufficient conditions for oscillation of all solutions. Finally, two examples are presented to illustrate the theoretical results.